The Function Of Virtual Media In Javanese Makeup Learning In Mike Up's Practice Lecture On Putri Cantik Jawa - Sawitri Sawitri; Pujiyana Pujiyana; Nurpeni Priyatiningsih; Sutarman Sutarman (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
The purpose of this study was to find out how to use virtual methods to increase student interest in learning Javanese makeup related to Javanese makeup. The type of this research is that students are given virtual video tutorials on how to make eyebrows, apply powder and foundation, and apply lipstick. Practice will get maximum results, it requires a process of repeated practice. Perseverance in following video tutorials that are practiced at home to get good results. The results will be seen when students send videos to lecturers which are sent individually from each student. Conclusion: Students' abilities can be seen from the results of videos made with models of themselves or others or taking turns with friends. Ability can be seen in the results of makeup, eyebrow shape, cheek rus shape, eye shadow coloring, the resulting shape of the face becomes more beautiful, clean and beautiful.